Nonstationary Temperature Distribution and Thermal Stresses in a Layered Elastic or Viscoelastic Medium - H. Bufler; G. Meier (Engineering Transactions)
A formal solution based on integral transforms and matrix analysis is given for the nonstationary fields of temperature, heat flux, stresses and displacements of a multilayered elastic medium. Non-linearities, inertia- and coupling effects are not taken into account. The applicability of the theory is demonstrated by means of numerically worked out examples. Extension to viscoelastic media is indicated.